Determinants of Digital Transformation in South African Telecommunication Organisations - Tar-Mahomed, Taazmin (University of the Witwatersrand, Johannesburg, 2024)
In the dynamic gig economy, organisations are grappling with increasing pressure to adapt through digital transformation (DT) for continued relevance. Successful DT initiatives have proven to boost organisational performance and competitive advantage, resulting in a twofold increase in total enterprise value for digital companies. However, despite its strategic significance, the intricate and multifaceted nature of factors that influence DT contributes to consistently low success rates in adopting this initiative. This study employed a qualitative research approach to develop a comprehensive DT framework, incorporating perspectives on strategy, technology and employee engagement. This involved a literature review of five seminal frameworks, which led to the conceptualisation of an artefact framework. The framework underwent rigorous evaluation through 15 semi-structured interviews with experts in digital transformation and telecommunications. The findings from the expert interviews informed the design of a holistic proposed framework anchored in the Digital Dynamic Capabilities Theory and Business Strategy Framework. The proposed framework delineates crucial determinants of DT that are tailored for South African telecommunication organisations. It comprises six pillars, which are grouped into visionary, structural and foundational enablers and encapsulate nuanced perspectives on technology, strategy, employee engagement and change management dynamics. The framework aims to serve as a best practice guide for industry leaders, emphasising the development of the capabilities, mindsets and structural conditions necessary for a successful DT journey.
A research report submitted in partial fulfillment of the requirements for the degree of Master of Management in the field of Digital Business to the Faculty of Commerce, Law, and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: Digital transformation; Key enabling factors; Key determinants; Telecommunications; UCTD; SDG-8: Decent work and economic growth